Exploring the needs and experiences of educators in facilitating use of the Bass Model of Holistic Reflection. (July 2020) - Bass, Janice; Sidebotham, Mary; Creedy, Debra; Sweet, Linda
Abstract: Health professionals are required to reflect on practice to evaluate and improve care in rapidly changing health care environments. This study explored the professional development needs of educators facilitating development of reflective capacity in midwifery students using the Bass Model of Holistic Reflection. Thirteen midwifery academics at two Australian universities took part in the study conducted in three phases. Phase 1 identified the learning needs of educators described as 'understanding the building blocks of reflection' ; ' practical application of the model, and 'assessment of reflective capacity' . Phase 2 involved an Intervention including development of a reflective practice tool kit and delivery of a two-day workshop. Phase 3 evaluated the experience of educators using the resources and four themes emerged: 1) ' Educators value a reflective practice toolkit '; 2) ' A toolkit builds confidence and trust in the model through promotion of deep personal reflection' ; 3) ' Effective use of the model is key to achieving consistency in application by educators ; and 4) ' Deeper understanding of the model promotes transformation of practice '. This paper confirms the importance of developing resources for educators, that support reflective pedagogy when implementing models of reflection into curricula. Highlights: Reflective skill development requires effective facilitation and role modelling. The Bass Model provides educators with a resource to scaffold reflective capacity. The toolkit supports consistency of application of the Bass Model by educators. Embedding reflective pedagogy in curricula builds reflective capacity. Educators require a tool capable of measuring the holistic continuum of reflection.